Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To simplify the expression [tex]\( 7^{-\frac{5}{6}} \cdot 7^{-\frac{7}{6}} \)[/tex], we can use the properties of exponents. Specifically, we use the property that states:
[tex]\[ a^m \cdot a^n = a^{m+n} \][/tex]
Here, our base [tex]\( a \)[/tex] is 7, and the exponents are [tex]\(-\frac{5}{6}\)[/tex] and [tex]\(-\frac{7}{6}\)[/tex]. We add these exponents together to combine them into a single exponent:
[tex]\[ -\frac{5}{6} + -\frac{7}{6} = -\left(\frac{5}{6} + \frac{7}{6}\right) = -\frac{5 + 7}{6} = -\frac{12}{6} = -2 \][/tex]
This means:
[tex]\[ 7^{-\frac{5}{6}} \cdot 7^{-\frac{7}{6}} = 7^{-2} \][/tex]
Next, we simplify [tex]\( 7^{-2} \)[/tex]. The property of negative exponents states:
[tex]\[ a^{-m} = \frac{1}{a^m} \][/tex]
Using this property, we get:
[tex]\[ 7^{-2} = \frac{1}{7^2} \][/tex]
We know that [tex]\( 7^2 = 49 \)[/tex], so:
[tex]\[ 7^{-2} = \frac{1}{49} \][/tex]
Therefore, the simplified expression is:
[tex]\[ \boxed{\frac{1}{49}} \][/tex]
[tex]\[ a^m \cdot a^n = a^{m+n} \][/tex]
Here, our base [tex]\( a \)[/tex] is 7, and the exponents are [tex]\(-\frac{5}{6}\)[/tex] and [tex]\(-\frac{7}{6}\)[/tex]. We add these exponents together to combine them into a single exponent:
[tex]\[ -\frac{5}{6} + -\frac{7}{6} = -\left(\frac{5}{6} + \frac{7}{6}\right) = -\frac{5 + 7}{6} = -\frac{12}{6} = -2 \][/tex]
This means:
[tex]\[ 7^{-\frac{5}{6}} \cdot 7^{-\frac{7}{6}} = 7^{-2} \][/tex]
Next, we simplify [tex]\( 7^{-2} \)[/tex]. The property of negative exponents states:
[tex]\[ a^{-m} = \frac{1}{a^m} \][/tex]
Using this property, we get:
[tex]\[ 7^{-2} = \frac{1}{7^2} \][/tex]
We know that [tex]\( 7^2 = 49 \)[/tex], so:
[tex]\[ 7^{-2} = \frac{1}{49} \][/tex]
Therefore, the simplified expression is:
[tex]\[ \boxed{\frac{1}{49}} \][/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.